The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1117/12.813650
|View full text |Cite
|
Sign up to set email alerts
|

Use of effective detective quantum efficiency to optimise radiographic exposures for chest imaging with computed radiography

Abstract: The purpose of the work was to test if effective detective quantum efficiency (eDQE) could be useful for optimisation of radiographic factors for computed radiography (CR) for adult chest examinations. The eDQE was therefore measured across a range of kilovoltage, with and without an anti-scatter grid. The modulation transfer function, noise power spectra, transmission factor and scatter fraction were measured with a phantom made of sheets of Aluminum and Acrylic. The entrance air kerma was selected to give an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
(12 reference statements)
2
7
1
Order By: Relevance
“…For approximately matched detector entrance air kerma (Table 1), the eDE is highest at 50 kVp and decreases as the tube voltage increases. This result is similar to that reported by Ertan et al [45], who found that eDE was superior at low tube voltages on a CR system from the same vendor (Agfa) as that employed here, as did Samei et al [23], albeit with an integrated digital imaging system. of 0.77 (p,0.008) was found; both the mean eDE kV_X and VGAS increase as the tube voltage decreases.…”
Section: Discussionsupporting
confidence: 81%
“…For approximately matched detector entrance air kerma (Table 1), the eDE is highest at 50 kVp and decreases as the tube voltage increases. This result is similar to that reported by Ertan et al [45], who found that eDE was superior at low tube voltages on a CR system from the same vendor (Agfa) as that employed here, as did Samei et al [23], albeit with an integrated digital imaging system. of 0.77 (p,0.008) was found; both the mean eDE kV_X and VGAS increase as the tube voltage decreases.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, the results for the W/Rh combination were greater for the grid-in case. Furthermore, these results showed close agreement with a non-prewhitened match filter with eye response model observer (d') normalized for MGD.The quantities effective detective quantum efficiency (eDQE) and effective noise equivalent quanta (eNEQ) can be seen as a development of the work of Wagner et al [1] , by Samei et al [2] and Ertan et al [3] with application to digital radiographic systems. The eDQE is an attempt to broaden the notion of the detector centric metric of detective quantum efficiency (DQE) to include system parameters such as focus blurring and system scatter rejection methods.…”
supporting
confidence: 67%
“…In the works of Samei et al [2] and Ertan et al [3] the MTF was calculated from an edge placed on the top of the phantom. This configuration introduces a low frequency drop (LFD) in the MTF curve, even if a small region of interest (ROI) is used to calculate the MTF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detective quantum efficiency (DQE) determines the ability of a detector to transfer the signal-to-noise ratio (SNR) within the detector as a function of spatial frequency [ 10 ]. The DQE helps characterise digital image detectors and has been used to compare detectors [ 11 , 12 ]. However, DQE is not optimal for assessing overall image quality and performance of the entire imaging system because it does not include impact from the magnification, focal spot blurring, the appearance of scatter radiation generated by the patient, or the presence of anti-scatter grids [ 13 ].…”
Section: Introductionmentioning
confidence: 99%